Single-cell transcriptomic landscape reveals complex cellular heterogeneity and dysregulated signaling pathways in nasopharyngeal carcinoma - Xiaoyan Zhang; Zuojia Guan; Zhan Xu (Discover Oncology)
Abstract Background Nasopharyngeal carcinoma (NPC) is a common malignancy with a complex pathogenesis and diverse cellular composition. This study aimed to systematically analyze the transcriptional characteristics of different cell types in NPC and their roles in tumor development using single-cell transcriptomics. Methods The research team collected NPC and normal tissue samples, and performed in-depth single-cell sequencing analysis of the transcriptomes. Single-cell RNA sequencing was performed on the collected samples to obtain high-resolution transcriptional profiles of individual cells. This allowed the researchers to identify and characterize the diverse cell populations present within the NPC tumor microenvironment. Results The results showed that NPC samples contained multiple distinct cell subpopulations, including epithelial cells, immune cells (such as macrophages and T cells), endothelial cells, and stromal cells. These cell types exhibited marked differences in spatial distribution and transcriptional profiles, reflecting the high degree of heterogeneity within the tumor microenvironment. Further functional analysis revealed significant dysregulation of mitochondrial-related pathways, extracellular matrix-receptor interactions, as well as Wnt, Notch, and other signaling cascades in NPC. Conclusion This study employed single-cell transcriptomics to comprehensively elucidate the complexity of the NPC tumor microenvironment, providing new insights into the underlying mechanisms of disease pathogenesis and suggesting potential therapeutic targets. These findings lay the groundwork for the development of precision medicine approaches for NPC.